You are on page 1of 8

SEMINAR REPORT ON Cayley-Hamilton Theorem

Submitted by: Name: Himanshi Section: ‘D’ Roll No:43

ai(t) = tjeait which appear in (3) since p(s) is the denominator of every entry of (sI ¡ A)¡1.Cayley Hamilton If p(s) is the characteristic polynomial of A then p(A) = 0. The characteristic polynomial of A. If Equation (3) is differentiated l times and then evaluated at 0 we get (4) Al =Xm i=1 nXi¡1 j=0 . determines the series 'j. p(s) = Qm i=1(s ¡ ai)ni . Proof.

. so that the argument applies in the more general setting of • matrices over a field of characteristic 0.• The Cayley Hamilton theorem on the characteristic • polynomial of a matrix A and Frobenius’ theorem on minimal polynomial • of A are deduced from the familiar Laplace transform formula • L(eAt) = (sI ¡ A)¡1. This formula is extended to a formal • power series ring over an algebraically closed field of characteristic • 0.

All = ~(A) If ~(A) is the characteristic polynomial of a matrix A. &(A) =A2 +A =[ ~ ~] .. eAt.e. Ak The Cayley-Hamilton theorem is essential to achieving this goal.g. then ~(A) = 0 implies that ~(A) = 0. Example Show thatA satisfies its own characteristic equation where A =O 1 0 -1 Solution Ans. e. i. A satisfies its own characteristic equation. cos(A). The Cayley-Hamilton Theorem LetIA .• • • • • • • • • • • • • • • Our main goal is to compute functions of a square matrix.

Proof of the CAYLEY HAMILTON Theorem • Let A be nxn with eigenvalues Ai‘ i=I.. 2.n-2 + . + B 1A.. for example 201 A=110 342 2-A 0 1 A-AI = 1 I-A 0 3 4 2-A In general. + B 0 . then ~(A) = IA-All = ( -A)n +c n-l An-l +c n-2 An-2+ .n-l + B n-2 A...(A ) = ( -A )n +c An-l +c An-2 +.. .c 1A+C0 need to show I 1. .. not necessarily distinct.A..I ) = Bn-l A. AdJ• (A .+c A+c 1=0 n-l n-2 1 0 consider Adj(A .AI).n..

Difference Equation Solutions Ans . Solution lo 1} By Cayley-Hamilton.x(k+1) == Ax(k) + Bu(k) Find x(k) == g(x(O).. u(i)) i == 0.1. k-I k-I Ans. x(k) =AkX(O)+ L Ak-I-lBu(i) 1=0 By induction.. (xCI) == Ax(O) + Bu(O) Example Q:-Find Ak if 1 1 1 11 x(k+ 1) = I x(k) + (-I)k xeD) = 0 1 1 11 Note that A is a Jordan form.. .AkJ 1 k .

Prove the Cayley-Hamilton theorem. Find Ak for a discrete-time system. Find eAt using Laplace transforms.USAGE • • • • • Find functions of a square matrix. Find eAt. .